Features Self-Cobalt Gas-sensitive Film of Polyacrylonitrile - S.P. Konovalenko; T.A. Bednaya (Журнал нано- та електронної фізики)
In this work gas-sensitive films of kobalt-containing polyacrylonitrile(PAN) are considered . Gas-sensitive characteristics of the obtained films of oxidizing gases to nitrogen of dioxideand chlorine are investigated. The images of surfaces of samples of films obtained using atomic force microscopy. The analysis of morphology of a surface with the theory of self-organization with use of a method of an investment of Takens and algorithm of Grassberger-Procaccia is carried out. The coefficient of increase in surface area, and size of correlation and fractal dimension of samples of filmsis calculated. It is establishedthat modifying t PAN materials with transition metals (cobalt)  with different percentage concentration and using of various time-temperature modes of her formation leads to change of morphology of a surface of films. Influence of temperature of pyrolysis of samples and mass content of the alloying component on formation of fractal structures in the studied materials is estimated.